PENGARUH PRAKTIK GREEN SUPPLY CHAIN MANAGEMENT TERHADAP KINERJA KEUANGAN DENGAN KEUNGGULAN BERSAING SEBAGAI VARIABEL MEDIASI: Studi Empiris pada Perusahaan Manufaktur di Kota Tangerang dan Kota Cilegon - Maharani, Sifa; Bastian, Elvin (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
The purpose of this study is to look at the impact of green supply chain management (gscm) practices on financial performance with competitive advantage serving as a mediating variable. The sample in this study amounted to 56 respondents from middle managers in Manufacturing Companies in Tangerang City and Cilegon City using the purposive sampling method. This is a quantitative study that uses primary data gathered from questionnaire distribution responses, which were then analyzed using SmartPLS software version 4.1. The results of this study indicate that Green Supply Chain Management (GSCM) has a positive and significant effect on Competitive Advantage, Green Supply Chain Management (GSCM) has a positive and significant effect on Financial Performance, Competitive Advantage has a positive and significant effect on Financial Performance, and Competitive Advantage can mediate the relationship between the influence of GSCM on Financial Performance.